Embedding transferrable skills into the higher degree by research candidature. (14th October 2019) - Milos, Dani
Abstract : Purpose: Higher degree by research (HDR) graduates are often perceived to be overly specialised and are unable to adapt to non-academic settings (Jaeger and Rudra, 2013 ). Universities are under increasing pressure to embed research and transferrable skills into the candidature in a flexible and meaningful way to equip graduates with the skills to succeed in a range of careers. The paper aims to study how Flinders University has embedded the Research and Employability Skills Training (REST) Program into the HDR. Design/methodology/approach: REST was established to replace the workshop-based professional development program, with a structured, compulsory, comprehensive program for HDR students, based on the Vitae Researcher Development Framework (RDF). The Program aims to provide students with the research skills they need to complete their studies and the transferrable skills employers seek, through an online, supported program that helps them identify their needs, plan and control their skills development. Such a comprehensive online candidature management system has enabled Flinders to implement the RDF and successfully and comprehensively embed REST into the HDR candidature, assisting students to articulate and demonstrate their skills with documented evidence. Findings: The Program has been running for one year, and so far, has been successful. Students are increasingly completing the initial online Skills Needs Analysis assessment component, which helps to identify their skills gaps and recommend workshops to meet their needs. Supervisors and students are engaging with the Program through structured discussion and refection of skills at each annual milestone, thanks to the help of the Inspire online candidature management system. Originality/value: REST is a valuable resource for HDR students, providing them with a range of skills to progress with their research, writing and professional development training that complements, but is separate from, their degree. Providing a structured training program which follows and supports students' candidature, and is based around the training needs and career trajectories of the student assists the students be more equipped and supported to complete on time and are well prepared for a range of career outcomes.